IDEOLOGISASI MAZHAB SYIAH DI BALIK PERIODISASI SEJARAH TAFSIR AL-QUR’AN - Musolli - (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2015)
This paper will examine the penetration of the Shia’s ideology in the periodization of the Qur’anic exegesis (Tafsir). It argued that periodization phases showed the evidence of the ideologization tracing back to the Shia’s exegetic activities by using the the theories of Gramsci’s hegemony and counter-hegemonies. This paper revealed also that, as opposed to Sunni Qur’anic exegesis, the Shia’s Qur’anic exegesis reached its peak at the period of ahl al-Bayt.Keywords: Shi’ah, Tafsir al-Qur’an, Ideologi, Periodisasi.